Comparison and optimization of two extract methods (atmospheric pressure and pressurized pretreatment) of pectin from Zanthoxylum bungeanum Maxim. seeds by response surface methodology. Issue 11 (24th July 2017) - Song, Yan; Ke, Jingxuan; Li, Shanshan; Shen, Guanghui; Luo, Qingying; Wu, Hejun; Liu, Xinyan; Chen, Anjun; Zhang, Zhiqing
ABSTRACT: In this study, the extract methods of pectin from Zanthoxylum bungeanum Maxim. seeds under atmospheric pressure and pressurized pretreatment were investigated and compared. Response surface methodology was applied to optimize the extraction conditions for obtaining the maximum yield of pectin. The optimum extraction conditions under atmospheric pressure were as follows: pH 2.5, 84.8°C, 81.0 min, and liquid-to-solid ratio 14.2:1 (ml/g). The optimum extraction conditions under pressurized pretreatment were as follows: pH 6.1, 117.7°C, and 95.4 min. In contrast, the optimal extraction yield under pressurized pretreatment was 76.52% above that of extraction under atmospheric pressure.